EVALUATION OF THE DHARMASRAYA-PADANG ROUTE TARIFFS ON TPN TRAVEL USING THE COST OF GOODS SOLD (COGS), ABILLITY TO PAY (ATP), AND WILLINGNESS TO PAY (WTP) METHODS - Muhammad Radian Alfariz; Kumala Dewi, Nurlaela; Mediyanti Pakpahan, Hartati (Organisasi Kreatif Indonesia Emas, 2024)
With the increase in fuel prices impacting the fare rates of Total Persada Nusantara (TPN) travel service on the Dharmasraya-Padang route, the fare has risen from IDR 100,000 to IDR 120,000. This change has led to a decrease in public interest in using this transportation service in Dharmasraya Regency. Therefore, an evaluation of the travel fare for this route is necessary to determine whether the TPN fare is appropriate or if a reduction is needed. This evaluation will be based on the fare derived from the calculation of Cost of Goods Sold (COGS), as well as using the Ability To Pay (ATP) and Willingness To Pay (WTP) methods to assess the extent of users' ability and willingness to pay for the travel fare. The results of the calculations show that the fare derived from the Cost of Goods Sold (COGS) is IDR 91,472, the average fare based on Ability To Pay (ATP) is IDR 1,598,985, and the average fare based on Willingness To Pay (WTP) is IDR 115,660.